Sub-channel analysis of lead–bismuth fast reactor fuel assembly with wire spacers for China initiative accelerator driven system. (1st June 2022) - Liu, Jia-Tai; Peng, Tian-Ji; Wang, Guan; Su, Xing-Kang; Tao, Yu-Jie; Fan, Da-Jun; Li, Xian-Wen; He, Ming-Han; Xu, Hu-Shan; Gu, Long
Highlights: The structure and models of the subchannel code are described. Critical validation with experience is carried out and discussed. The relevant calculation results of CiADS are analyzed in detail. Abstract: The lead bismuth eutectic (LBE) cooled fast reactor fuel assemblies in China Initiative Accelerator Driven subcritical System (CiADS) are supported by wire spacers, and the sub-channel code is a significant analysis method to evaluate the thermal–hydraulic behavior of fuel assemblies. In this study, a sub-channel analysis code for LBE coolant is developed, in which the pressure drop model, turbulent mixing model, and heat transfer model based on LBE are added and applied. Besides, the heat transfer experience of the 61-pin fuel assembly and other sub-channel codes are chosen to verify. Finally, the full-scale simulation of CiADS fuel assembly is calculated. The results show that the thermal–hydraulic parameters of CiADS meet the design criterion. The optimized range of pitch to diameter ratio is 1.133–1.145 according to the thermal–hydraulic analysis. It is recommended to use 37-pin bundle for the numerical simulation simplification of full-scale rod bundles.